Correcting unfolded helix in a 22-year-old male patient: a case report - Si hyun Ahn; Hojin Park (Archives of Aesthetic Plastic Surgery)
An unfolded helix is an auricular deformity that has garnered relatively little research focus. This study introduces a surgical technique designed to correct flat helix deformities. A 22-year-old male with bilateral unfolded helixes and prominent ears underwent this procedure under local anesthesia. The surgery employed a posterior auricular approach, with incisions extending from the upper pole of the ear to the concha. Along the helical rim, four radiating incisions were made, followed by oblique cuts in the cartilage and the creation of triangular flaps through advancement. The free edges of the cartilage were then overlapped and sutured together. Post-surgery, the patient experienced a successful recovery, evidenced by the curling of the helix and the absence of complications. This surgical technique is not only effective for correcting unfolded helixes but can also be efficiently performed under local anesthesia.